The Best Wife is an Obedient Wife. Is the Best Husband Just Any Husband? On the Means and Differences in Expressing Marital Love in the Sixteenth-Century Wills of Lwow Towns-people - Knajp, Marta J. (1994– ) (Fundacja Instytutu Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The paper focuses on marital feelings recorded in the last wills of sixteenth-century townspeople of Lwow (Lviv). By comparing the wills of women and men, differences and similarities in the manifestation of positive emotions towards spouses were identified. The information contained in the analysed wills made it possible to determine the qualities that townspeople desired in their husbands and wives. Additionally, the potential reasons and consequences of recording information about marital love were examined.
p. 49-63
Keywords: sixteenth century; Lwow (Lviv); Lviv (Ukraine) - 16th century; family; marriage; emotions in history